2021
DOI: 10.1371/journal.pcbi.1009136
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional analysis and detection of informative features in human brain white matter

Abstract: The white matter contains long-range connections between different brain regions and the organization of these connections holds important implications for brain function in health and disease. Tractometry uses diffusion-weighted magnetic resonance imaging (dMRI) to quantify tissue properties along the trajectories of these connections. Statistical inference from tractometry usually either averages these quantities along the length of each fiber bundle or computes regression models separately for each point al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 90 publications
(135 reference statements)
1
18
0
Order By: Relevance
“…In a recent study, age has been accurately predicted by FA and ADC metrics. 105 These results justify as well that if taking into account the microstructural measures, age is of critical importance in distinguishing between the two motor groups.…”
Section: Discussionmentioning
confidence: 66%
“…In a recent study, age has been accurately predicted by FA and ADC metrics. 105 These results justify as well that if taking into account the microstructural measures, age is of critical importance in distinguishing between the two motor groups.…”
Section: Discussionmentioning
confidence: 66%
“…Failure to do so may cause spurious associations or degrade predictive performance. To demonstrate this, we selected participant age as a representative phenotypic benchmark because (i) it operates on a natural scale with meaningful units and (ii) despite the unique methodological challenges it presents for biomarker identi cation ( Nelson et al, 2020 ), brain age prediction may be diagnostic of overall brain health ( Franke et al, 2010 ; Cole et al, 2019 ; Richie-Halford et al, 2021 ). We observed the effect of varying QC cutoff on the predictive performance of an age prediction model.…”
Section: Resultsmentioning
confidence: 99%
“…We retain only the mean diffusivity (MD) and the fractional anisotropy (FA) from a diffusion kurtosis imaging (DKI) model ( Jensen et al, 2005 ), implemented in DIPY ( Henriques et al, 2021 ), and impute missing bundles using median imputation as implemented by scikit-learn ’s . Because the HBN-POD2 bundle profiles exhibit strong site effects ( Richie-Halford et al, 2021 ), we used the ComBat harmonization method to robustly adjust for site effects in the tract profiles. Initially designed to correct for site effects in gene expression studies ( Johnson et al, 2007 ), ComBat employs a parametric empirical Bayes approach to adjust for batch effects and has since been applied to multi-site cortical thickness measurements ( Fortin et al, 2018 ), multi-site DTI studies ( Fortin et al, 2017 ), and functional MRI data in the Adolescent Brain Cognitive Development Study (ABCD) ( Nielson et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBN dataset was selected because the age range was appropriate for the desired age-based analysis, and because many of the MRI scans were known to be corrupted with artifacts based on our prior experience with this dataset ( Luna et al, 2021 ). Prior research has demonstrated a linear relationship between participant age and FA ( Rathee et al, 2016 ; Richie-Halford et al, 2021 ). Exploiting this fact, a proof-of-concept analysis examined the bivariate correlation between mean whole-brain FA and participant age.…”
Section: Methodsmentioning
confidence: 97%